Horticulture based farming system model for income and livelihood - Kashyap, Poonam; Panwar, A S; Prusty, A K; Singh, M P; Verma, Nisha; Shamim, M; Kumar, Sunil; Jat, P C; Kumar, Devendra; Kumar, Sumit (Indian Farming, 2021)
The integrated farming systems approach is considered to be most powerful tool for enhancing profitability of farming systems, especially for small and marginal farm-holders. In fact, our past experience has clearly evidenced that the income from cropping alone is hardly sufficient to sustain the farmers’ needs. With changing scenario, farmers’ requirements for cash have also increased to improve their standard of living. In this context, horticulture provides excellent opportunities in raising the income of farmers even under abrasive conditions. The cultivation of fruit and vegetables under horticulture based farming plays an important role in the prosperity of nation along with health, happiness and prosperity. ICAR-Indian Institute of Farming Systems Research (IIFSR), Modipuram, Meerut has been undertaking research activities at farmers’ field under Farmer FIRST Programme (FFP). Through horticulture based farming systems, the resources are effectively utilized, conserved well and improves environment.